Modelling and parameter estimation of dynamic systems - Raol, J. R. (Jitendra R.) 1947-; Girija, G. 1954- (Gopalrathnam); Singh, J. Ph.D (Institution of Engineering and Technology, 2004)
The book is written at postgraduate level and comprised N chapters dealing with the following topics: modelling; parameter estimation; dynamic systems; least squares method; output error method; filtering methods; filter error method; model error determination; and model error concept.